An architectural design and evaluation of an affective tutoring system for novice programmers - FWA, Hua Leong (Institutional Knowledge at Singapore Management University, 2018)
Affect is prevalent in learning and it influences students’ learning achievement. This paper details the design and evaluation of an Affective Tutoring System (ATS) that tutors student in computer programming. Although most ATSs are purpose built for a specific domain, making adaptation to another domain difficult, this ATS is architected for adaptability and extensibility. This study also addresses a lack of research exploring the theories and methods of integrating affect and learning within the learning process by proposing methods of regulating the negative affect of students. Both quantitative and qualitative techniques were used for evaluation of the effectiveness of the ATS and its usability and acceptance by student participants. The results revealed that the full affective version of the ATS results in more effective tutoring as compared to the version with the affective function disabled and the students are positive on their learning experience with the ATS with the fill in the gap exercises and hints being most highly rated.